“It's a war! It's a battle! It's a fight!”: do militaristic metaphors increase people's threat perceptions and support for COVID-19 policies? - Schnepf, Julia; Christmann, Ursula (International journal of psychology, 2021)
At the beginning of the COVID-19 pandemic, governments around the world employed militaristic metaphors to draw attention to the dangers of the virus. But, do militaristic metaphors truly affect individuals' perceived threat of the COVID-19 virus and increase their support for corresponding restrictive policies? This study assessed the effects of fictitious newspaper articles that described COVID-19 policies using similarly negatively valenced metaphors but with differing militaristic connotations (e.g., “war” vs. “struggle”). Overall, data from three framing experiments (N = 1114) in Germany and the United States indicate limited evidence on the effectiveness of the tested militaristic metaphors. In the U.S. context, the non-militaristic concept of struggle was consistently more strongly associated with the desired outcomes than militaristic metaphors were. In Studies 2 and 3, we also tested whether reporting using a narrative or straightforward facts had additional influence on the framing effect. A congruency effect of the use of a narrative and of warfare metaphors was found in the German sample, but not in that of the United States. Results of post-experimental norming studies (N = 437) in both countries revealed that the metaphor of war is associated with people ascribing greater responsibility to their governments, whereas the concept of struggle triggers a sense of individual responsibility. These results are discussed in terms of the usefulness and appropriateness of militaristic metaphors in the context of a pandemic.
Gesehen am 04.11.2021
Epub ahead of print